Influence of a lordotic cage profile on global and segmental lordosis in the context of lumbar TLIF surgeries: a retrospective radiological analysis - Schulz, Steffen; Fennema, Peter; Darwich, Ali; Bludau, Frederic; Rickert, Marcus (Journal of Clinical Medicine, 2024)
Background/Objectives: Cage implantation decompresses neural elements, stabilizes segments, and promotes fusion, with sagittal balance influenced by cage size, geometry, and position. This retrospective study compared the effects of lumbar interbody cages with 10° and 15° lordotic angles on global and segmental lordosis in patients undergoing transforaminal lumbar interbody fusion (TLIF). Methods: Data from 215 patients who underwent 259 TLIF procedures between 2018 and 2022 were analyzed. All the surgeries were performed by a single senior orthopedic spine surgeon, and cages were selected by the surgeon based on patients’ clinical and anatomical factors. Radiographic assessments included measurements of global and segmental lordosis. Results: Patients who received 15° cages demonstrated significantly greater segmental lordosis compared to those who received 10° cages in both bisegmental and monosegmental procedures (p < 0.001). While the global lordosis in the 10°-cage group remained unchanged postoperatively (p = 0.687), bisegmental procedures showed a small but statistically significant increase (p = 0.035). Moreover, global lordosis did not significantly differ between the 10°- and 15°-cage groups. Conclusions: Cage geometry significantly influenced segmental lordosis, with 15° cages achieving overall more superior radiographic results compared to 10° cages. However, global lordosis was unaffected by cage angle, thereby highlighting the multifaceted nature of factors that influence overall spinal alignment. These findings provide valuable insights into lumbar spine surgery, thus emphasizing the need for comprehensive preoperative planning and consideration of individual patient characteristics.
Gesehen am 22.04.2025